Protective Behavioral Strategies Moderate the Association between Narcissistic Traits and Alcohol Pathology in College Student Drinkers. (16th April 2019) - Kramer, Matthew P.; Wilborn, Dexter D.; Spencer, Christopher C.; Stevenson, Brittany L.; Dvorak, Robert D.
Abstract: Background : Personality traits found in Cluster B personality disorders have garnered considerable empirical attention and have been linked to a litany of issues, such as alcohol-related problems. While psychopathic traits have been linked to alcohol-use consequences, narcissistic traits remain understudied. Objectives : The current study examines the relationship between narcissistic traits and alcohol use and consequences as a function of Protective Behavioral Strategies (PBS) in a sample of college students. Method : Participants ( n = 387 college student drinkers; 69.25% female) completed a series of questionnaires assessing alcohol use and consequences, PBS use, and narcissistic traits. Results : There was a significant positive association between narcissistic traits and alcohol use and consequences. The interaction of PBS and narcissistic traits was also statistically significant. Simple slopes revealed that at high levels of PBS (+1 SD ), the relationship between narcissistic traits and alcohol-use consequences was attenuated and not significant, while at low levels of PBS (–1 SD ), this association was potentiated. Conclusion : These findings suggest that interventions targeting PBS use may be one way to reduce alcohol problems among those with higher levels of narcissistic traits.